Effect of Maternal and Post-Weaning Folate Supply on Gene-Specific DNA Methylation in the Small Intestine of Weaning and Adult Apc+/Min and Wild Type Mice - Mckay, Jill A.; Williams, Elizabeth A.; Mathers, John C. (Frontiers in Genetics, 2011)
Increasing evidence supports the developmental origins of adult health and disease hypothesis which argues for a causal relationship between adverse early life nutrition and increased disease risk in adulthood. Modulation of epigenetic marks, e.g. DNA methylation and consequential altered gene expression, has been proposed as a mechanism mediating these effects. Via its role as a methyl donor, dietary folate supply may influence DNA methylation. As aberrant methylation is an early event in colorectal cancer (CRC) pathogenesis, we hypothesised low maternal and/or post-weaning folate intake may influence methylation of genes involved in CRC development. We investigated the effects of maternal folate depletion during pregnancy and lactation on selected gene methylation in the small intestine (SI) of wild type (WT) and Apc+/Min mice at weaning and as adults. We also investigated the effects of folate depletion post-weaning on gene methylation in adult mice. Female C57Bl6/J mice were fed low or normal folate diets from mating with Apc+/Min males to the end of lactation. A sub set of offspring were killed at weaning. Remaining offspring were weaned on to low or normal folate diets, resulting in 4 treatment groups of Apc+/Min and WT mice. p53 was more methylated in weaning and adult WT compared with Apc+/Min mice (p>0.001). Igf2 and Apc were hypermethylated in adult Apc+/Mi n compared with WT mice (p=0.004 & p=0.012 respectively). Low maternal folate reduced p53 methylation in adults (p=0.04). Low post-weaning folate increased Apc methylation in Apc+/Min mice only (p=0.008 for interaction). These observations demonstrate that folate depletion in early life can alter epigenetic marks in a gene specific manner. Also, the differential effects of altered folate supply on DNA methylation in WT and Apc+/Min mice suggest that genotype may modulate epigenetic responses to environmental cues and may have implications for the development of personalised nutrition.